Extra-articular Distal Tibial Fracture: A Comparative Study of the Outcome Between Closed IMLN and MIPO - Abdulrahim, Yad Atuf; Al-Tamimi, Ali Abdalnabi Alwan (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: The treatment of distal tibial fractures (DTF) is still up for debate. For DTF, minimally invasive plate osteosynthesis (MIPO) and intramedullary nailing (IMLN) are potentially effective techniques; however, they have been linked to complications. Thus, this study was aimed to evaluate and compare clinical and functional results in individuals with DTF that were managed with MIPO or IMLN. Patients and Methods: Between August 2020 and February 2022, 31 patients with closed extra-articular distal tibia fractures were enrolled in a comparative study of locking plate by MIPO versus closed IMLN at the Sulaimani Teaching Hospital and Shar Teaching Hospital. The Foot and Ankle Ability Measure (FAAM) and Johner and Wruh's criteria were used to evaluate the results. Results: IMLN was used on 16 individuals, while MIPO was used on 15 patients that underwent surgery. In terms of time, there was no significant difference (p>0.05) in fracture union, malunion, or functional results. However, there was a significant difference in total weight-bearing following surgery, blood loss, and complications in terms of the operation time. Conclusions: Both techniques were effective in treating a distal tibial extra-articular fracture. IMLN had a faster complete weight-bearing time and a shorter operation time. At the same time, MIPO had less blood loss and equal time in complete union. Thus, we recommend using FAAM as a valuable tool in evaluating functional outcomes after distal tibia fracture.
Keywords: Tibial fracture; prospective study; advanced technique; FAAM; Sulaimani city